Utilization of Power Setting in Monopolar Electrosurgery Unit With Additional Blend Modes - Setiawan, Muhammad Roni; Indrato, Tri Bowo; Rahmawati, Triana; Utomo, Bedjo (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
There is one fundamental thing that says electrosurgery is dangerous because of the lack of understanding of the monopolar technology in ESU can produce a larger current and will spread more widely throughout the body compared to bipolar. So in this study, the objective of this research is to develop a monopolar electrosurgery unit equipped with an additional mixed-mode and also equipped with a power selection. The contribution of this research is designing power management and adding several modes for the surgical process. The module is calibrated using the ESU Analyzer. This module comes with a choice of low, medium, and high power. And there are also several additional modes including blend 1 and blend 2. After the measurement, the value of the voltage at the inverter input shows the value for blend 1 mode, low 80 V with an error of 0.84%, Medium 90 V with an error of 0.84%, High 104 V with an error of 0.81. %. The measurements show an error of less than 1% for Blend 1 and also in Blend 2, while a cut is less than 3%. The results of this study can be implemented to minimize errors due to a lack of power regulation and mode selection during operation for electrosurgery equipment